Education and nation building - Hashim, Rosnani (Thomson Learning, 2008)
Malaysia is a multiethnic society where various racial grous live peacefully with one another. It is blessed with a visionary leadership and a sound education system.Education plays a significant role in Malaysia's development of its human resource and economy. Countries with multi-racial and multi-religious populations can benefit from the Malaysian experience.